Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1592/phco.31.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure contributes to more than 1 million hospitalizations annually and is one of the most common causes of repeat hospitalizations in the elderly. Previously, it was thought that mortality from heart failure with preserved ejection fraction (PEF) was lower than that from heart failure with reduced ejection fraction (REF), but more recent data infer similar mortality. Although the mortality rate in patients with heart failure with REF is decreasing, the mortality rate in patients with heart failure with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Our study suggests that patients with HFrEF were more likely to be initiated on GDMT compared to those with HFpEF. This finding is not surprising considering the lack of evidence supporting GDMT in patients with HFpEF (7). A retrospective analysis of elderly patients with HFpEF enrolled in the OPTIMIZE-HF study reported no improvement in mortality or rehospitalization with newly started BB therapy (25).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our study suggests that patients with HFrEF were more likely to be initiated on GDMT compared to those with HFpEF. This finding is not surprising considering the lack of evidence supporting GDMT in patients with HFpEF (7). A retrospective analysis of elderly patients with HFpEF enrolled in the OPTIMIZE-HF study reported no improvement in mortality or rehospitalization with newly started BB therapy (25).…”
Section: Discussionmentioning
confidence: 82%
“…In HFrEF, GDMT includes angiotensin-converting enzyme inhibitors (ACEI) (or angiotensin-receptor blockers (ARB) in ACEI-intolerant patients) and β blockers (BB) in all patients, as well as aldosterone-receptor antagonists (ARA), digoxin, nitrates, and hydralazine in select patients. Unfortunately, no therapy has shown a mortality benefit in patients with HF with preserved ejection fraction (HFpEF) (7).…”
mentioning
confidence: 99%
“…4,6 LCZ696 is a new combination drug of the angiotensin II type 1 receptor (AT 1 ) blocker (ARB) valsartan and the neprilysin inhibitor prodrug AHU377 that has been developed by Novartis. This dual combination exerts a powerful vasodilatory and natriuresis effect by blocking angiotensin II activity on the one hand, while augmenting plasma levels of natriuretic peptides, such as BNP, on the other.…”
Section: Drugs In the Pipelinementioning
confidence: 99%
“…Careful laboratory monitoring is required on commencement and follow‐up. Finally, through analysis in the conduct of such large‐scale trials it is critical to inform patient care and future research …”
Section: Mineralocorticoid Receptor Antagonismmentioning
confidence: 99%